Plio-Pleistocene Carnivora of North-western Africa : a short review - (:unkn) unknown (My University, 2008)
The richest assemblage is that of the Late Pliocene of Ahl al Oughlam, with more than 20 species belonging to the main modern families. Some additions to its study [11] are made here. The rather poor Early Pleistocene faunas are mainly marked by the arrival of a large Canis. A fauna of modern type, with e.g., the duo Hyaena - Crocuta, settles in the earliest Pleistocene site of Tighenif, where some older elements linger on (Homotherium), beside some taxa of doubtful affinities, like a large Panthera, and a strange canid close to Nyctereutes, dominant at this site as well as at the slightly younger ones of Thomas and Oulad Hamida Quarries in Casablanca. All these faunas consist mostly of African taxa, together with a Palaearctic component whose importance increases towards the end of the Pleistocene.
Keywords: African Research